Struktur Kalimat Bahasa Paser Dialek Telake - Iskandar, Andi Firdaus; Mulawarman, Widyatmike Gede; Ahmad, M. Rusydi (Universitas Mulawarman, 2018)
The syntax can help researchers to analyze the structure of phrases, clauses, or sentences of certain regional languages. Things that can be analyzed as sentence types, sentence functions, and categories contained in sentence functions. The purpose of this study is to describe the structure of sentence functions in the Paser language of the Telake dialect, Paser Regency, and the categories that can fill each sentence function in the Paser language of the Telake dialect. This type of research is descriptive qualitative research. The descriptive qualitative research method is defined as research that examines natural social action events emphasizing the way people interpret, and understand the structure of sentence functions and the categories that can fill each sentence function in the Telake dialect Paser language. To obtain the primary data, the writer uses (a) observation technique, (b) recording technique, (c) listening technique, (d), note-taking technique, and (e) introspection technique. The data is then classified according to the research indicators to achieve the research objectives that have been set. The results of the research on the functions and categories of sentences in the Paser language of the Telake dialect show that the functions and categories of sentences in the Telake Paser dialect are in the types of sentences (1) singular, (2) compound, (3) declarative, (4) imperative, (5) interrogative, (6) exclamative, (7) major, and (8) minor.